Thursday

April 24, 2014

April 24, 2014

Posted by **-Untamed-** on Saturday, December 31, 2011 at 7:51pm.

(3t^2+3t-6/2t^2-2t-4)(4t^2+4t-24/3t^2+6t-9)

This is the way I tried solving this:

3t(t-1)6(t-1)/2t(t-1)4(t-1)*4t(t-2)12(t-2)/3t(t+1)9(t-1)

(3)(t)(t-1)(2)(3)(t-1)/(2)(t)(t-1)(2)(2)(t-1)*(2)(2)(t)(t-2)(2)(2)(3)(t-2)/(3)(t)(t-1)(3)(3)(t-1)

After cancelling out all the terms I am left with:

(2)(t-2)(t-2)/(t-1)(t-1)

^ I cant cancel anything off now. But the answer is supposed to be :

2(t+2)/t+1

^ How do I get that answer?

- Calculus -
**Damon**, Saturday, December 31, 2011 at 8:12pm(3t^2+3t-6)(4t^2+4t-24)

===============================

(2t^2-2t-4)(3t^2+6t-9)

3(t^2+t-2)(4)(t^2+t-6)

==============================

2(t-2)(t+1)(3)(t+3)(t-1)

3(t+2)(t-1)(4)(t+3)(t-2)

==============================

2(t-2)(t+1)(3)(t+3)(t-1)

(2) (t+2) / (t+1)

2

- Calculus -
**-Untamed-**, Saturday, December 31, 2011 at 8:17pmThank you so much Damon :)

- Calculus -
**Damon**, Saturday, December 31, 2011 at 8:21pmYou are welcome.

By the way that is undefined if t = -1 so I suppose that might be what is meant by "non-permissible"

- Calculus -
**-Untamed-**, Saturday, December 31, 2011 at 8:25pmThank you and yeah nonpermissible is another word for restrictions.

**Related Questions**

calculus - Let f(t)=2t²+3t-4 f(t+1)=f(t)+4t+5 TRUE or FALSE answer is true, but ...

ALGEBRA/PLEASE HELP - have the answer and would love confirmation. VERY ...

Math - Using factoring by grouping, how would you factor these out. 4t^2+3t-4t-3...

math - Using factoring by grouping, how would you factor these out. 4t^2+3t-4t-3...

ALGEBRA - I have the answer and would love confirmation. VERY APPRECIATED! Find ...

calculus - Find parametric equations for the line through the point P(2, 9, 4) ...

math - solve. 6t + 7/ 4t - 1 = 3t +8/2t - 4

math - (5t^4 + 6t^3 – 3t^2 + 4t - 11) - (-9t^4 – 6t^3 + 5t^2 + 3t + 8) Simplify ...

Math Uugghhh - Okay the problem says I have to multiply (-2t)^2(3t^7)^2 SO what ...

science - position of a particle in frame s is given by r=(6t^2-4t)i-3t^3j+3k.in...